2010
DOI: 10.1063/1.3409870
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of gas adsorption on graphene nanoribbons

Abstract: We present a theory to study gas molecules adsorption on armchair graphene nanoribbons (AGNRs) by applying the results of ab initio calculations to the single-band tight-binding approximation. In addition, the effect of edge states on the electronic properties of AGNR is included in the calculations. Under the assumption that the gas molecules adsorb on the ribbon sites with uniform probability distribution, the applicability of the method is examined for finite concentrations of adsorption of several simple g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…The adsorption of NH 3 molecule converts the electronic structure of 6-AGNR as a degenerate semiconductor. These results are consistent with those obtained by Huang et al [22] and Saffarzadeh [24].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The adsorption of NH 3 molecule converts the electronic structure of 6-AGNR as a degenerate semiconductor. These results are consistent with those obtained by Huang et al [22] and Saffarzadeh [24].…”
Section: Discussionsupporting
confidence: 83%
“…However DFT calculations show that AGNRs are semiconducting with a finite band gap and the value of the gap depends on their width [19][20][21]. Theoretical and ab initio studies of GNRs sensing properties have been reported already, showing that absorption of CO 2 or O 2 molecules changes the AGNR to p-type semiconductor, while NH 3 adsorption changes it to a n-type semiconductor [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…6b) for A 7 GNR, the CO (NH 3 ) adsorbed molecule induces quasi-localized state in the band gap, which is located near and above the Fermi level (near the conduction band) without any changing in the position of the HOMO and LUMO states in good agreement with previous study. 14 The decreasing of the concentration of gas leads to decreasing the intensity of the induced states (see Fig. 6).…”
Section: Density Of Statesmentioning
confidence: 99%
“…For the center region by N S atoms and N G molecule adsorption, the gas concentration is determined as c ¼ N G N s . 14 In this study we suppose N G = 1. The possibility weight of each configuration can be attributed to the adsorption energy [E ads = E adsorbed À (E pristine + E molecule )] with the linear relation.…”
Section: Model and Formalismmentioning
confidence: 99%
See 1 more Smart Citation